IMPLEMENTASI BIMBNGAN MINAT BACA ALQURAN DI SMK BAITUL HIKMAH TEMPUREJO JEMBER - Abdul Halim (Universitas Islam Negeri Sumatera Utara Medan, 2019)
School is an environment where students get formal education and teaching. When entering school age the child has obtained reading lessons. One of the facilities to help the teaching and learning process in schools is the school library. Through various sources in the library, both students and teachers can interact and be directly involved both physically and mentally in the teaching and learning process. So that the school library is really used efficiently. With these activities it is hoped that reading interest will grow and develop into a reading fondness. The utilization of libraries in Baitul Hikmah Vocational School is good. Seen there is a means to read the Koran provided in the library building. The reading practice of the Qur'an Vocational Baitul Hikmah is accustomed every day from Monday to Saturday before the scheduled school hours start. Teacher guides reading the Koran are usually led by subject teachers who hold the first hour schedule. The impact of reading the Koran is very big felt by the students themselves, for the school, and for parents. The impact on students personally is more fluent and fluent in reading the Koran, and behave politely to parents, and the community. The impact on schools is that students are more easily controlled. The impact on parents is that students are more obedient. The consequence is that the community is very sympathetic to the Baitul Hikmah Vocational School, which is busy entering their children into the school. Keywords: Guidance, reading interest, Al-Qur'an